New options for subgingival oral hygiene with a flattened interdental brush design: in vitro examination and case report - Staehle, Hans Jörg; Kim, Ti-Sun; Sekundo, Caroline (Oral health & preventive dentistry, 2023)
Purpose: The subgingival area is only reached to a limited extent during home oral hygiene with the aids available to date. The question was investigated whether a newly developed, flattened cross-sectional design of interdental brushes (IDBs) can extend their subgingival reach. - Materials and ...
Gesehen am 10.07.2023